Evaluation and Treatment of Baseball Pitchers: There’s More to Assess than the Arm - Matthew L Gauthier; Casey A Unverzagt; George J Davies (International Journal of Sports Physical Therapy)
Injuries are commonplace in the overhead athlete, with many occurring to the shoulder and elbow. The increasing prevalence of injuries to the shoulder and elbow has been discussed at length in recent years, with increased research focus being placed on arm care for rehabilitation and prevention strategies. Even though the pitching motion is well-established as a whole-body kinetic chain movement, most attention in rehabilitation and prevention efforts is often placed on the upper extremity. The purpose of this clinical commentary is to highlight the impact the lower extremity and trunk have on the upper extremity during the throwing motion, better equipping clinicians to treat this patient population. Additionally, this clinical commentary highlights the current literature and recommendations regarding examination of the entire kinetic chain and concludes with a review of current evidence and recommendations regarding treatment of impairments and functional limitations identified in the proximal kinetic chain. In leaving no stone unturned, clinicians can address all components of the kinetic chain in throwers, maximizing performance and mitigating risk of injury. Level of Evidence: 5